EFEKTIVITAS PENERAPAN METODE AL-MIFTAH LI AL-ULUM DALAM BELAJAR MEMBACA BUKU KLASIK DI PP. NURUL JADID PAITON PROBOLINGGO - Fathor Rozi; Ahmad Zubaidi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Al-Miftah li al Ulum is a fast method of reading a classical book that was initiated directly by a senior teacher at the Sidogiri Islamic Boarding School in Pasuruan, including one of the learning methods that has an extraordinary appeal towards learning to read the classical book because it uses brief explanations but understands and how to memorize Arabic lafadz positions and formulas which are packaged in Indonesian verses. Reading the classical book becomes a rare habit. This might be due to the fact that there is no or less interesting method used. Along with the emergence of some interesting methods of reading classical book, the students seemed to find a new paradigm in learning the yellow book. Based on the background above, what we want to know is about the effectiveness of the application of the al-Miftah li al-Ulum method in learning to read the classical book in Madrasah Diniyah Fatimatuzzahro’ PP. Nurul Jadid Islamic Boarding School Paiton Probolinggo. Furthermore, according to its type, this research is a qualitative case study type using observation, documentation, and interview methods in the process of collecting data. While the data analysis is an interactive analysis of Miles & Huberman by reducing data, displaying data, verifying data, and finally making conclusions.